2017
DOI: 10.1103/physrevb.96.245419
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the thermal conductance of molecular junctions with interference effects

Abstract: We present an ab initio study of the role of interference effects in the thermal conductance of single-molecule junctions. To be precise, using a first-principles transport method based on density functional theory, we analyze the coherent phonon transport in single-molecule junctions made of several benzene and oligo-phenylene-ethynylene derivatives. We show that the thermal conductance of these junctions can be tuned via the inclusion of substituents, which induces destructive interference effects and result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 72 publications
3
56
0
1
Order By: Relevance
“…More importantly, the destructive interference features of those crossconjugated molecules significantly reduce the thermal conductance with respect to linear conjugated analogues. Recently, Klockner et al used a DFT‐based first‐principles method to analyze the coherent phonon transport in single‐molecule junctions made of several benzene derivatives (Figure d) . They showed that the thermal conductance of these MJs can be tuned via the inclusion of substituents, which also induces destructive interference effects and results in a decrease of the thermal conductance with respect to the unmodified molecules (Figure f).…”
Section: Thermal Properties Of Molecular Junctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the destructive interference features of those crossconjugated molecules significantly reduce the thermal conductance with respect to linear conjugated analogues. Recently, Klockner et al used a DFT‐based first‐principles method to analyze the coherent phonon transport in single‐molecule junctions made of several benzene derivatives (Figure d) . They showed that the thermal conductance of these MJs can be tuned via the inclusion of substituents, which also induces destructive interference effects and results in a decrease of the thermal conductance with respect to the unmodified molecules (Figure f).…”
Section: Thermal Properties Of Molecular Junctionsmentioning
confidence: 99%
“…F) The corresponding phononic thermal conductance as a function of temperature for the different benzenediamine derivatives. The inset shows the room‐temperature cumulative thermal conductance as a function of energy for the junctions with X = H, Br, I. D–F) Reproduced with permission . Copyright 2017, American Physical Society.…”
Section: Thermal Properties Of Molecular Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, by looking in details at the phonon transmissions for dibenzylbenzene and diphenoxybenzene shown in Figure 7b, we observe that in the former case T() is characterized by several Fano-like features throughout the spectrum. Famili et al [26] and Klockner et al [27] discussed how the emergence of phononic Fano interferences could lead to a low thermal conductance in molecular bridges. Fano resonances could arise because the CH2 linkers have masses and therefore vibrational frequencies in resonance with those of the benzene rings, whereas the mass mismatch of the oxygens breaks the mode degeneracies, removing destructive interferences in the transmission.…”
Section: Aromatic Molecular Junctionsmentioning
confidence: 99%
“…Fano effect, that is the effects of interference between a continuum and a resonant state, is important in the interpretation of electronic transport [25]. Indeed, Famili et al and Klockner et al have found that this effect modifies the phonon transport of molecular junctions [26,27]. For phonon transport, the Fano effects occur under Debye energies, for metallic electrodes that is typically in the range of several tens of meV (10 meV≃80.64 cm -1 ) 1 , while for graphene, the Debye temperature of ΘD ≈ 2100K makes that Fano effect limit to 1459.6 cm −1 which gives a wide window of phonon energies that contributes to thermal transport at room temperatures [28].…”
Section: Introductionmentioning
confidence: 99%